Study of Aeromycoflora in the Indoor Environment of College Library: Assessment of Airborne Fungal Diversity and Its Impact on Book Preservation in a College Library (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Air Sampling study was undertaken by adopting culture plate technique, method (CPT),aeromycoflora intramural sampling performed in the library of the Govt. College of EducationAurangabad, was investigated for a period from November 2020 to February 2021. Altogetherthirteen types of fungal colonies were identified of which61.53 of the genera belonged toDeuteromycotina, 23.07, to Ascomycotina 7.69 to Zygomycoting and 7.69 to unidentified. Amongthe thirteen genera identified 9 are reported to cause damage and deterioration of books and papermaterials They are Mucor, Rhizopus, Aspergillus, Cladosporium, Curvularia, Alternaria, Penicillium,Fusarium and Epicoccum. Concentration of fungal colonies was maximum in March followed by Apriland minimum in January. The concentration of fungal colonies was maximum in December 50 followedby November -47, January-- 44 and February -43. The present work was carried out to identify and findout the component and contribution percentage of airborne fungi inside the college library and theirrelevance to book deterioration.